Improving the Use of Digital Marketing in Increasing Competitiveness of Businesses Operating in Uzbekistan's B2c Sector (Eurasian Scientific Herald, 2023)
Although the role and importance of digital marketing in the B2C (business-toconsumer) sector is very high today, its implementation and effectiveness depends on the nature of industries and types of companies. This article identifies the specific aspects of using digital marketing to increase the competitiveness of businesses operating in the B2C sector in today's competitive environment.